PROSCRIPTION AND RADICALIZATION: THE NIGERIAN GOVERNMENT’S BAN ON IPOB AND ITS SECURITY IMPLICATIONS - Nkata, Roberts Anya; Okpan, Samuel Okpanocha (African Journal of Social and Behavioural Sciences, 2025)
This article critically examines the Nigerian government's decision to proscribe the Indigenous People of Biafra (IPOB) and classify it as a terrorist organization. It explores the implications of this designation on the group's radicalization, insecurity, and the resulting effects on the socio-economic development of the Southeast region of Nigeria. Drawing from three theoretical frameworks—labelling theory, grievance-based rebellion theory, and structural repression theory—as well as secondary data collected from newspapers, magazines, and journal articles, the study seeks to determine the extent to which the designation of terrorism and the proscription of IPOB have contributed to the group's radicalization and subsequent increase in insecurity, ultimately destabilizing the socio-economic development of the region. The study found among others that proscription of IPOB has impacted negatively on socio-economic growth of the region. It revealed that the sit-at-home order caused over 80% loss of revenue. The paper concludes with recommendations for fostering dialogue and addressing the underlying grievances in Nigeria's Southeast region.